PENGGUNAAN APLIKASI E-KINERJA SEBAGAI BAGIAN DARI STRATEGI PENGEMBANGAN PEMERINTAHAN ELEKTRONIK DENGAN TUJUAN MENINGKATKAN KINERJA PEGAWAI - Rauf, Eka Ubaya Taruna; Wisnaningsih, Wisnaningsih; Juwita, Farida (Jurnal Progress Administrasi Publik, 2024)
The purpose of this study was to determine the Implementation of the E-Performance Application Policy at the Bandar Lampung City Human Resources Development and Personnel Agency and to determine the Development of E-Government at the Bandar Lampung City Human Resources Development and Personnel Agency. Data collection techniques were carried out through observation, interview, and documentation methods. By using qualitative data analysis. An important finding in this study is that there are still a number of employees who have not fully mastered the procedure for compiling Employee Work Targets (SKP) through an online system. In addition, there are also ASN who tend to underestimate the importance of filling out performance reports online, so they are often late in fulfilling these obligations. This condition is especially seen in ASN with older ages and those who are highly dependent on the performance of third-party servers that support the E-Performance application. The results of the study indicate that with the presence of E-Performance, employee performance at the Bandar Lampung City BKPSDM can be improved through improved communication, efficient use of resources, and improvements to the work system. The implementation of e-government at the Bandar Lampung City BKPSDM is a positive step in improving the quality of public services. However, a number of challenges still need to be overcome, such as limited employee understanding of the e-performance system and dependence on third-party infrastructure. To overcome this, ongoing efforts are needed in terms of increasing employee capacity and developing a more independent technology infrastructure. Thus, BKPSDM Bandar Lampung City can be more optimal in providing effective and efficient public services.   Keywords: Application; E-Performance; Strategy; Employee; Development